Annual variation in recruitment and age-specific survival of Little Penguins, Eudyptula minor. (1st March 2016) - Agnew, Philippa; Lalas, Chris; Wright, Janine; Dawson, Steve
Abstract: Identifying variation in survival probabilities is fundamental to understanding population dynamics. We quantified variation in survival of Little Penguins ( Eudyptula minor ) at Oamaru, New Zealand, over 19 years from 1993–2011. Specifically survival in relation to age and breeding status were investigated. We used a multi-state capture-mark-recapture model to examine survival and recapture probabilities of known age penguins flipper-banded as chicks, and breeding penguins of unknown age banded as adults. The survival probability of Little Penguins in their first year averaged 0.42 and was lower than all older ages. The mean annual survival probability of breeding adult penguins was 0.86. The observed proportion of fledglings that later recruited into the breeding population in the study colony mirrored first-year survival estimates from the model. Survival was lower for pre-breeding penguins than for breeding penguins of the same age. We detected no significant effect of age on survival for breeding penguins. The comprehensive, long-term monitoring program in place at Oamaru resulted in very high recapture rates of breeding penguins that generated accurate estimates of survival.